Prevalence of Internet Addiction and Its Associated Factors Among Undergraduate Students at the University of Botswana: A Cross-Sectional Study. - Keutule, Lorato; Molebatsi, Keneilwe; Olashore, Anthony A. (Inquiry (00469580), 2026)
Internet Addiction (IA) is an emerging public health concern, especially among young adults. It has been associated with various psychiatric conditions, including depression and anxiety. Despite increasing internet access in Botswana, local data on IA and its psychological correlates remain limited. This study investigates the prevalence and patterns of internet addiction and its association with depression and anxiety among undergraduate students at the University of Botswana. A cross-sectional study was conducted among 500 undergraduate students from 5 randomly selected faculties. Participants completed the Young Internet Addiction Test (YIAT), Patient Health Questionnaire-9 (PHQ-9), and Zung Self-Rating Anxiety Scale (SAS). Data were analyzed using descriptive statistics and multiple linear regression. The mean age was 21.42 years (SD = 4.36); 52.2% were female. The prevalence of IA was 88.4%. Social networking was the most common reason for internet use (91.8%). High depression scores were observed in 64% of participants, and moderate anxiety levels in 47%. Depression (B = 0.26; P <.001), anxiety (B = 0.12; P <.02), and time spent online (B = 0.33; P <.001) were significant predictors of IA. IA is common among university students in Botswana and is linked to depression and anxiety. These findings underscore the importance of routine screening, education, and psychological support in universities.